Słowacka proza naturyzmu w polskich przekładach — strategie wyboru i translacji w zmieniającej się perspektywie kulturowej drugiej połowy XX wieku - Buczek, Marta (Przekłady Literatur Słowiańskich, 2018)
Slovak Naturalist Prose in Polish Translations — Strategies for Selection and Translation in the Changing Cultural Perspective of the Second Half of the Twentieth Century The author of the article analyses Polish translations of the Slovak naturalist prose which is a very interesting phenomenon at the primary horizon and appears to be the most frequently translated into Polish. The author concentrates on the representative translations, strategies for selection and strategies for translation of the naturalism in the changing cultural perspective of the second half of the twentieth century. Historical and cultural situation, historical distance between the originals and their translations has the biggest influence for the selection of the texts but also for the strategies the translators choose during the process of translation. In the perspective of cultural and literature turn in Poland in 1956, the Slovak naturalist prose had the chance to appear in the second horizon but it did not affect recipients and did not have the possibility to impact the development of the receiving literature. The author of the article tries to answer the question why it did not happen. KEY WORDS: literary translation, Slovak prose of naturizmus, Slovak literature in Polish translation, Margita Figuli, Ľudo Ondrejov, Dobroslav Chrobák, František Švanter